2010
DOI: 10.1139/v10-023
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of model triazene-based anticancer agents

Abstract: A computational study of a series of model triazene-based anticancer agents based on methyl- and amidyl-substituted 5-(1-triazenyl)imidazoles has been carried out, including the drugs Dacarbazine, Temozolomide, and Mitozolomide. A number of different conformers are analyzed. The transition states for the gas-phase and water-mediated triazene tautomerization reaction are found and the barriers are determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The MTICs produced from path-1 and path-2 are tautomeric forms, whereas the water-mediated energy barrier for this 1,3-hydrogen shi is 5.93 kcal mol À1 . 36 The energy diagram for both pathways reveals that in spite of the lower TS-I for path-1, the TS-II and obtained products are more energy favoured for the second path. It appears that TMZ would prevail over ring opening in the more energy favoured path-1 that forms the rst MTIC tautomer but then undergoes tautomerism to generate the next MTIC tautomer (Scheme 1), which decomposes through the second path.…”
Section: Hydrolytic Degradation Mechanism Of Tmz To Mticmentioning
confidence: 95%
“…The MTICs produced from path-1 and path-2 are tautomeric forms, whereas the water-mediated energy barrier for this 1,3-hydrogen shi is 5.93 kcal mol À1 . 36 The energy diagram for both pathways reveals that in spite of the lower TS-I for path-1, the TS-II and obtained products are more energy favoured for the second path. It appears that TMZ would prevail over ring opening in the more energy favoured path-1 that forms the rst MTIC tautomer but then undergoes tautomerism to generate the next MTIC tautomer (Scheme 1), which decomposes through the second path.…”
Section: Hydrolytic Degradation Mechanism Of Tmz To Mticmentioning
confidence: 95%
“…The addition of the LUVs decreased the absorbance of TMZ very slightly and gradually, while maintaining the shape of the spectrum, which discards drug degradation and suggests some interaction between the drug and the lipid membrane. The small decrease in absorbance could be explained by the existence in solution of two stable rotamers of TMZ [59]. Recently, Khallilian et al reported that the rotation of carboxamide moiety in TMZ leads to two rotamers with slight differences in their extinction coefficients and dipole moments; Rotamer 1 being more stable than Rotamer 2 [60].…”
Section: Interaction Of Tmz With Model Membranesmentioning
confidence: 99%